Construction of an Acetate Metabolic Pathway to Enhance Electron Generation of Engineered Shewanella oneidensis - Zhang, Junqi; Chen, Zheng; Liu, Changjiang; Li, Jianxun; An, Xingjuan; Wu, Deguang; Sun, Xi; Zhang, Baocai; Fu, Longping; Li, Feng; Song, Hao (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Microbial fuel cells (MFCs) are a novel bioelectrochemical devices that can use exoelectrogens as biocatalyst to convert various organic wastes into electricity. Among them, acetate, a major component of industrial biological wastewater and by-product of lignocellulose degradation, could release eight electrons per mole when completely degraded into CO2 and H2O, which has been identified as a promising carbon source and electron donor. However, Shewanella oneidensis MR-1, a famous facultative anaerobic exoelectrogens, only preferentially uses lactate as carbon source and electron donor and could hardly metabolize acetate in MFCs, which greatly limited Coulombic efficiency of MFCs and the capacity of bio-catalysis. Results: Here, to enable acetate as the sole carbon source and electron donor for electricity production in S. oneidensis, we successfully constructed three engineered S. oneidensis (named AceU1, AceU2, and AceU3) by assembling the succinyl-CoA:acetate CoA-transferase (SCACT) metabolism pathways, including acetate coenzyme A transferase encoded by ato1 and ato2 gene from G. sulfurreducens and citrate synthase encoded by the gltA gene from S. oneidensis, which could successfully utilize acetate as carbon source under anaerobic and aerobic conditions. Then, biochemical characterizations showed the engineered strain AceU3 generated a maximum power density of 8.3 ± 1.2 mW/m2 with acetate as the sole electron donor in MFCs. In addition, when further using lactate as the electron donor, the maximum power density obtained by AceU3 was 51.1 ± 3.1 mW/m2, which approximately 2.4-fold higher than that of wild type (WT). Besides, the Coulombic efficiency of AceU3 strain could reach 12.4% increased by 2.0-fold compared that of WT, which demonstrated that the engineered strain AceU3 can further utilize acetate as an electron donor to continuously generate electricity. Conclusion: In the present study, we first rationally designed S. oneidensis for enhancing the electron generation by using acetate as sole carbon source and electron donor. Based on synthetic biology strategies, modular assembly of acetate metabolic pathways could be further extended to other exoelectrogens to improve the Coulombic efficiency and broaden the spectrum of available carbon sources in MFCs for bioelectricity production.